2015
DOI: 10.1155/2015/780451
|View full text |Cite
|
Sign up to set email alerts
|

A Minimally Invasive Endoscopic Surgery for Infectious Spondylodiscitis of the Thoracic and Upper Lumbar Spine in Immunocompromised Patients

Abstract: This study evaluates the safety and effectiveness of computed tomography- (CT-) assisted endoscopic surgery in the treatment of infectious spondylodiscitis of the thoracic and upper lumbar spine in immunocompromised patients. From October 2006 to March 2014, a total of 41 patients with infectious spondylodiscitis underwent percutaneous endoscopic surgery under local anesthesia, and 13 lesions from 13 patients on the thoracic or upper lumbar spine were selected for evaluation. A CT-guided catheter was placed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…In Table 4, we compare our data with recently published studies on spontaneous spondylodiscitis. 3,7,9,18,22,23,[30][31][32][33][34]36 Compared to other series, our study had a mean patient age that was younger by more than 10 years, 27% of our patients were managed conservatively, only 8.3% of the conservatively managed patients required surgery, and 30-day overall mortality was less than 5%. Our series is similar to the other series in its male predominance.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In Table 4, we compare our data with recently published studies on spontaneous spondylodiscitis. 3,7,9,18,22,23,[30][31][32][33][34]36 Compared to other series, our study had a mean patient age that was younger by more than 10 years, 27% of our patients were managed conservatively, only 8.3% of the conservatively managed patients required surgery, and 30-day overall mortality was less than 5%. Our series is similar to the other series in its male predominance.…”
Section: Discussionmentioning
confidence: 61%
“…33 In our series, 2 patients required fusion surgery after laminectomy because of uncontrollable pain. Although open surgery has been the technique of choice traditionally, new publications refer to endoscopic 7 and minimally invasive 34 techniques for spondylodiscitis management.…”
Section: Antibiotic Treatment Decompression and Instrumented Fusionmentioning
confidence: 99%
“…If significant publication bias was found, the Duval and Tweedie trim and fill method was used to adjust for the possible bias. bridement and drainage (PEDD), which is coupled with less complications and satisfactory clinical outcome, provides a minimally invasive surgical choice for the treatment of spinal infection (7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al . [ 4 ] reported quick pain relief from a VAS of 9.2–2.3 after MIS endoscopic surgery and antibiotic treatment for spondylodiscitis in a cohort of immunocompromised patients. Similarly, another group too reported that all patients showed immediate back pain reduction after surgery for discitis.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of MIS are all highly desirable features when treating patients with a suspected infection, especially since these patients are often sick or immunocompromised with multiple comorbidities. [ 4 5 6 7 ] This paper reports a series of patients with spinal infection in whom MIS techniques were employed to obtain a quick diagnosis to enable appropriate antibiotic therapy and faster recovery from pain, reduce the disease burden, and avoid a potentially bigger operation.…”
Section: Introductionmentioning
confidence: 99%